QISSALARDA SARGUZASHT UNSURLAR (Tohir Malik asarlari misolida) - Sapayeva, F.; D.Mirzayeva, O.Kurbanbayev, N.Xojaahmadova (SCIENCE and SOCIETY, 2022)
The article presents the artistic features of the stories of Tahir Malik, as well as problems with human spirituality in their stories, in which the elements of adventure are interpreted to one degree or another artistically. In the analysis of detective-adventure stories such as ”Shaytanat”, ”Goodbye childhood”, which received special love from readers, these issues were approached on the basis of new principles.
Keywords: story(narrative); uzbek literature; detective; adventure; substance; essence; writer